Anode active material, anode containing same, and secondary battery

The development of silicon-containing composite particles with a carbon layer and an amorphous surface layer addresses the challenges of irreversible capacity and moisture reactions in lithium secondary batteries, resulting in enhanced charging and discharging efficiency and improved battery performance.

JP7661504B2Active Publication Date: 2025-04-14LG ENERGY SOLUTION LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023541991
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-05-04
Filing Date
2022-08-09
Publication Date
2025-04-14
Estimated Expiration
2042-08-09

AI Technical Summary

Technical Problem

Existing negative electrode active materials for lithium secondary batteries, particularly silicon-containing oxides, face challenges with irreversible capacity, leading to reduced initial efficiency and defective electrodes due to reactions with moisture in the slurry.

Method used

A silicon-containing composite particle with a carbon layer and an amorphous surface layer containing Li, Al, and P is developed, which effectively removes lithium by-products, stabilizes the phase, and enhances lithium diffusion, thereby improving charging and discharging efficiency.

Benefits of technology

The proposed negative electrode active material achieves stable capacity and efficiency, reduces side reactions, and exhibits excellent discharge rate control properties, leading to improved battery performance and lifespan.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661504000004
    Figure 0007661504000004
  • Figure 0007661504000005
    Figure 0007661504000005
  • Figure 0007661504000006
    Figure 0007661504000006
Patent Text Reader

Abstract

The present invention relates to a method for producing a SiO x (0
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This application claims the benefit of the filing dates of Korean Patent Application No. 10-2021-0107524 filed with the Korean Intellectual Property Office on August 13, 2021, and Korean Patent Application No. 10-2022-0055522 filed with the Korean Intellectual Property Office on May 4, 2022, the entire contents of which are incorporated herein by reference.

[0002] The present invention relates to a negative electrode active material, a negative electrode containing the same, and a secondary battery. [Background technology]

[0003] In recent years, with the rapid spread of electronic devices that use batteries, such as mobile phones, notebook computers, and electric vehicles, the demand for small, lightweight, and relatively high-capacity secondary batteries is rapidly increasing. In particular, lithium secondary batteries, which are lightweight and have high energy density, have been attracting attention as a driving power source for portable devices. As a result, research and development efforts to improve the performance of lithium secondary batteries are being actively pursued.

[0004] In general, a lithium secondary battery includes a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte. In addition, the positive electrode and the negative electrode may have active material layers formed on current collectors, each of which includes a positive electrode active material and a negative electrode active material. In general, the positive electrode uses a lithium-containing metal oxide such as LiCoO2 or LiMn2O4 as a positive electrode active material, and the negative electrode uses a lithium-free carbon-containing active material or a silicon-containing active material as a negative electrode active material.

[0005] Among negative electrode active materials, silicon-containing active materials have been attracting attention because they have higher capacity and excellent high-speed charging characteristics compared to carbon-containing active materials. However, silicon-containing active materials have the disadvantage of low initial efficiency due to large volume expansion / contraction during charging / discharging and large irreversible capacity.

[0006] On the other hand, among silicon-containing active materials, silicon-containing oxides, specifically SiO xIn the case of a silicon-containing oxide represented by (0 < x < 2), there is an advantage in that the degree of volume expansion / contraction due to charge / discharge with respect to other silicon-containing active materials such as silicon (Si) is low. However, there is still a drawback that the initial efficiency of the silicon-containing oxide decreases due to the presence of irreversible capacity.

[0007] Regarding this, research has continued to reduce the irreversible capacity and improve the initial efficiency by doping or inserting metals such as Li, Al, and Mg into the silicon-containing oxide. However, in the case of a negative electrode slurry containing a metal-doped silicon-containing oxide as a negative electrode active material, there is a problem that the metal oxide formed by doping reacts with moisture to increase the pH of the negative electrode slurry and change the viscosity. That is, there is a problem that the state of the negative electrode manufactured thereby becomes poor and the charge / discharge efficiency of the negative electrode decreases.

[0008] Therefore, there is a current need to develop a negative electrode active material that can improve the phase stability of a negative electrode slurry containing a silicon-containing oxide and improve the charge / discharge efficiency of the negative electrode manufactured therefrom.

[0009] Korean Registered Patent No. 10-0794192 relates to a method for manufacturing a carbon-coated silicon-graphite composite negative electrode active material for a lithium secondary battery and a method for manufacturing a secondary battery including the same, but there are limitations in solving the above-described problems.

Prior Art Documents

Patent Documents

[0010]

Patent Document 1

Summary of the Invention

Problems to be Solved by the Invention

[0011] The present invention relates to a negative electrode active material, a negative electrode including the same, and a secondary battery.

Means for Solving the Problems

[0012] One embodiment of the present invention is silicon-containing composite particles containing SiO x (0 < x < 2) and a Li compound; a carbon layer on at least a part of the surface of the silicon-containing composite particles; a surface layer containing an amorphous phase on at least a part of the silicon-containing composite particles; and a negative electrode active material containing at least one Group 13 element and at least one Group 15 element are provided.

[0013] One embodiment of the present invention provides a negative electrode containing the negative electrode active material.

[0014] One embodiment of the present invention provides a secondary battery containing the negative electrode.

Advantages of the Invention

[0015] The negative electrode active material according to one embodiment of the present invention includes a surface layer provided on the silicon-containing composite particles, and the surface layer contains an amorphous phase. By providing such a surface layer on the surface of the silicon-containing composite particles, lithium by-products contained in the silicon-containing composite particles can be effectively removed, unreacted lithium by-products can be effectively coated, and the phenomenon that lithium by-products or lithium compounds in the silicon-containing composite particles react with the moisture of the slurry to deteriorate the physical properties of the slurry can be prevented. In addition, since the surface layer is formed of an amorphous phase and the entry and exit of Li ions are facilitated, there is an effect that the capacity, efficiency, resistance performance, and / or life of the battery can be stably realized while effectively reducing side reactions on the slurry.

[0016] Further, the negative electrode active material according to one embodiment of the present invention has a surface layer containing Li, and the lithium diffusion resistance on the surface of the negative electrode active material is low, and there is an effect of excellent rate capability.

[0017] The present invention will be more fully understood through the following detailed description and the accompanying drawings, which are provided by way of example only and do not limit the present invention. [Brief description of the drawings]

[0018] [Figure 1] 1 is a schematic diagram of a negative electrode active material according to one embodiment of the present invention, in which a carbon layer is coated on the surface of a silicon-containing composite particle, and a surface layer is coated on the carbon layer (e.g., the surface layer is a thin film). [Diagram 2] 1 shows an anode active material according to one embodiment of the present invention, in which a carbon layer is coated on the surface of a silicon-containing composite particle, and a surface layer is coated on a portion of the carbon layer (e.g., the surface layer is an island layer). [Diagram 3] 1 shows an anode active material according to one embodiment of the present invention having partially overlapping and non-overlapping layers of carbon and surface layers on silicon-containing composite particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] This specification will be explained in more detail below.

[0020] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.

[0021] In this specification, when we say that a member is located "on" another member, this includes not only when the member is in contact with the other member, but also when there is another member between the two members.

[0022] The terms or words used in this specification should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted as having a meaning and concept that matches the technical idea of ​​the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.

[0023] As used herein, the singular expression of a term includes the plural expression unless the context clearly indicates otherwise.

[0024] In the present specification, the crystallinity of the structure contained in the negative electrode active material may be confirmed by X-ray diffraction analysis. The X-ray diffraction analysis may be performed using an X-ray diffraction (XRD) analysis device (product name: D4-endavor, manufacturer: Bruker), and other devices used in the art may be appropriately adopted.

[0025] In this specification, the presence or absence of elements in the negative electrode active material and the content of the elements can be confirmed by ICP analysis, which can be performed using an inductively coupled plasma optical emission spectrometer (ICPAES, Perkin-Elmer 7300).

[0026] In this specification, the average particle size (D 50 The average particle size (D) can be defined as the particle size that corresponds to 50% of the cumulative volume in the particle size distribution curve (graph curve of the particle size distribution diagram). 50 ) can be measured, for example, by the laser diffraction method. The laser diffraction method generally allows measurement of particle sizes from the submicron range to about several mm, and can provide results with high reproducibility and high resolution.

[0027] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS The present invention will be described in detail below with reference to preferred embodiments thereof. However, the present invention can be modified in various ways, and the scope of the present invention is not limited to the embodiments described below.

[0028] <Negative electrode active material> One embodiment of the present invention is SiO xSilicon-containing composite particles comprising (0 < x < 2) and a Li compound; a carbon layer on at least a part of the surface of the silicon-containing composite particles; a surface layer containing an amorphous phase on at least a part of the silicon-containing composite particles; and a negative electrode active material containing at least one Group 13 element and at least one Group 15 element are provided.

[0029] Generally, lithium by-products formed by unreacted lithium are present on the particles during the process of doping silicon-containing particles with Li, and the slurry will become basic when the slurry is formed. Therefore, there is a problem that the rheological properties of the slurry change and gas is generated by the reaction of Si and the base in the silicon-containing particles.

[0030] Therefore, in the present invention, a surface layer is provided on the Li-doped silicon-containing composite particles to effectively remove the lithium by-products formed in the Li doping process, and the formed surface layer is formed on the silicon-containing composite particles and serves to passivate the particles. The surface layer formed at this time contains an amorphous phase, and since the entry and exit of Li ions are facilitated, there is an effect that the side reaction on the slurry can be effectively reduced while the capacity, efficiency, resistance performance, and / or life of the battery can be stably realized.

[0031] In addition, when the surface layer further contains Li, there is an effect that the lithium diffusion resistance on the surface of the negative electrode active material is lowered and the rate capability is excellent.

[0032] The negative electrode active material according to an embodiment of the present invention includes silicon-containing composite particles. The silicon-containing composite particles contain SiO x (0 < x < 2) and a Li compound, and a carbon layer is provided on at least a part of the surface.

[0033] The SiO x (0 < x < 2) can correspond to a matrix in the silicon-containing composite particles. The SiO x(0 < x < 2) may be in a form containing Si and SiO2, and the Si may form a phase. That is, the x corresponds to the number ratio of O to Si contained within (0 < x < 2). When the silicon-containing composite particles contain SiO x (0 < x < 2), the discharge capacity of the secondary battery can be improved. x (0 < x < 2), the discharge capacity of the secondary battery can be improved.

[0034] In one embodiment of the present invention, the silicon-containing composite particles may contain a Li compound.

[0035] The Li compound may correspond to a matrix within the silicon-containing composite particles. The Li compound can exist in at least one form of lithium atom, lithium silicate, lithium silicide, and lithium oxide within the silicon-containing composite particles. When the silicon-containing composite particles contain a Li compound, there is an effect of improving the initial efficiency.

[0036] The Li compound may be distributed on the surface and / or inside of the silicon-containing composite particles in a form doped into the silicon-containing composite particles. The Li compound is distributed on the surface and / or inside of the silicon-containing composite particles, can control the volume expansion / contraction of the silicon-containing composite particles to an appropriate level, and can play a role in preventing damage to the active material. Further, the Li compound may be contained in terms of reducing the ratio of the irreversible phase (for example, SiO2) of the silicon-containing oxide particles to increase the efficiency of the active material.

[0037] In one embodiment of the present invention, the Li compound may exist in the form of lithium silicate. The lithium silicate is Li a Si b O c(2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and can be classified into crystalline lithium silicate and amorphous lithium silicate. The crystalline lithium silicate can exist in the form of at least one lithium silicate selected from the group consisting of Li2SiO3, Li4SiO4, and Li2Si2O5 within the silicon-containing particles, and the amorphous lithium silicate is Li a Si b O c It may include a complex structure in the form of (2 ≤ a ≤ 4, 0 < b ≤ 2, 2 ≤ c ≤ 5), and is not limited to the above form.

[0038] In one embodiment of the present invention, when performing X-ray diffraction analysis on the negative electrode active material, peaks derived from Si may appear, and peaks derived from at least one of Li2SiO3 and Li2Si2O5 may also appear.

[0039] The peaks derived from Si may include diffraction peaks due to Si(111) and / or Si(220). The diffraction peak due to Si(111) may appear in the range of diffraction angle (2θ) = 27.5° to 29.5°, and the diffraction peak due to Si(220) may appear in the range of diffraction angle (2θ) = 45° to 50°.

[0040] The peak derived from Li2SiO3 may appear in the range of diffraction angle (2θ) = 17.5° to 20.5°, and the peak derived from Li2Si2O5 may appear in the range of diffraction angle (2θ) = 23.0° to 25.5°. However, the peaks derived from the above compounds may also include peaks that appear in other diffraction angle ranges outside the above diffraction angle ranges.

[0041] The X-ray diffraction analysis of the negative electrode active material can be performed using an X-ray diffraction (XRD) analyzer (product name: D4-endavor, manufacturer: Bruker). Specifically, an X-ray wavelength generated by Cu Kα can be used. 0.3 g of the negative electrode active material is placed in a cylindrical holder with a diameter of 2.5 cm and a height of 2.5 mm, and a flattening operation is performed with a slide glass so that the height of the sample in the holder is constant. After preparing the sample for XRD analysis, the SCAN TIME of the XRD analyzer is set to 1 hour and 15 minutes, the measurement area is set to a 2θ area of ​​10° to 90°, and the STEP TIME and STEP SIZE are set so that 2θ is scanned by 0.02° per second, and the peak can be measured.

[0042] In one embodiment of the present invention, Li may be included in an amount of 0.1 to 25 parts by weight based on a total of 100 parts by weight of the negative electrode active material. Specifically, Li may be included in an amount of 1 to 15 parts by weight, more specifically, Li may be included in an amount of 2 to 11 parts by weight. In one example, the Li content may be 4 parts by weight or more, 6 parts by weight or more, 8 parts by weight or more, or 10 parts by weight or less based on a total of 100 parts by weight of the negative electrode active material. As the Li content increases, the initial efficiency increases, but there is a problem that the discharge capacity decreases. Therefore, when the Li content is in the range of 0.1 to 25 parts by weight, it is possible to realize appropriate discharge capacity and initial efficiency.

[0043] The Li element content can be confirmed by ICP analysis. Specifically, a certain amount (about 0.01 g) of the negative active material is taken, transferred to a platinum crucible, and nitric acid, hydrofluoric acid, and sulfuric acid are added to it, followed by complete decomposition on a hot plate. Then, an inductively coupled plasma emission spectroscope (ICPAES, Perkin-Elmer 7300) is used to measure the intensity of a standard solution prepared using a standard solution (5 mg / kg) at the characteristic wavelength of the element to be analyzed, and a reference calibration curve is created. Then, the pretreated sample solution and the base sample are introduced into the device, and the respective intensities are measured to calculate the actual intensities, and the concentration of each component is calculated relative to the created calibration curve, and the element content of the negative active material produced can be analyzed by converting the total sum to a theoretical value.

[0044] In one embodiment of the present invention, the silicon-containing composite particles may include additional metal atoms. The metal atoms may be present in the silicon-containing composite particles in the form of at least one of metal atoms, metal silicates, metal silicides, and metal oxides. The metal atoms may include at least one selected from the group consisting of Mg, Li, Al, and Ca. This can improve the initial efficiency of the negative electrode active material.

[0045] The silicon-containing composite particles according to one embodiment of the present invention have a carbon layer on at least a part of the surface. In this case, the carbon layer may be in a form in which at least a part of the particle surface is coated. That is, the carbon layer may be in a form in which the particle surface is partially coated with the carbon layer, or in a form in which the particle surface is entirely coated with the carbon layer. The carbon layer imparts electrical conductivity to the negative electrode active material, and can improve the initial efficiency, life characteristics, and battery capacity characteristics of the secondary battery.

[0046] In one embodiment of the invention, the carbon layer comprises an amorphous phase.

[0047] Specifically, the carbon layer may include amorphous carbon. Alternatively, the carbon layer may be an amorphous carbon layer. The amorphous carbon can adequately maintain the strength of the carbon layer and suppress the expansion of the silicon-containing composite particles.

[0048] Additionally, the carbon layer may or may not further comprise crystalline carbon.

[0049] The crystalline carbon can further improve the electrical conductivity of the negative electrode active material. The crystalline carbon may include at least one selected from the group consisting of fullerene, carbon nanotube, and graphene.

[0050] The amorphous carbon can adequately maintain the strength of the carbon layer and suppress the expansion of the silicon-containing composite particles. The amorphous carbon may be at least one carbide selected from the group consisting of tar, pitch, and other organic substances, or a carbon-containing material formed using a hydrocarbon as a source for chemical vapor deposition.

[0051] The carbonized organic material may be a carbonized organic material selected from carbonized sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose or ketohexose, and combinations thereof.

[0052] The hydrocarbon may be a substituted or unsubstituted aliphatic or alicyclic hydrocarbon, or a substituted or unsubstituted aromatic hydrocarbon. The aliphatic or alicyclic hydrocarbon of the substituted or unsubstituted aliphatic or alicyclic hydrocarbon may be methane, ethane, ethylene, acetylene, propane, butane, butene, pentane, isobutane, hexane, etc. The aromatic hydrocarbon of the substituted or unsubstituted aromatic hydrocarbon may be benzene, toluene, xylene, styrene, ethylbenzene, diphenylmethane, naphthalene, phenol, cresol, nitrobenzene, chlorobenzene, indene, coumarone, pyridine, anthracene, phenanthrene, etc.

[0053] In one embodiment of the present invention, the carbon layer may be included in an amount of 0.1 to 50 parts by weight, 0.1 to 30 parts by weight, or 0.1 to 20 parts by weight based on a total of 100 parts by weight of the negative electrode active material. More specifically, the carbon layer may be included in an amount of 0.5 to 15 parts by weight, 1 to 10 parts by weight, 2 to 8 parts by weight, or 3 to 5 parts by weight. When the amount is within the range of 0.1 to 50 parts by weight, a decrease in capacity and efficiency of the negative electrode active material can be prevented.

[0054] In one embodiment of the present invention, the thickness of the carbon layer is 1 nm to 500 nm, and specifically, it may be 5 nm to 300 nm. When the range of 1 nm to 500 nm is satisfied, the conductivity of the negative electrode active material is improved, the volume change of the negative electrode active material is easily suppressed, the side reaction between the electrolyte and the negative electrode active material is suppressed, and the initial efficiency and / or life of the battery are improved.

[0055] Specifically, the carbon layer may be formed by chemical vapor deposition (CVD) using at least one hydrocarbon gas selected from the group consisting of methane, ethane, and acetylene.

[0056] The silicon-containing composite particles according to one embodiment of the present invention include a surface layer provided on at least a part of the silicon-containing composite particles.

[0057] The surface layer may be in a form covering at least a part of the silicon-containing composite particles having a carbon layer on the surface. That is, the surface layer may be partially covering the particle surface or may be in a form covering the entire particle surface. Examples of the shape of the surface layer include an island type or a thin film type, but the shape of the surface layer is not limited thereto.

[0058] The surface layer may be provided on at least a part of the outer surface of the carbon layer. That is, the surface layer is coated adjacent to the carbon layer and may be provided in the form of a particle-carbon layer-surface layer containing SiO x (0 < x < 2) and a Li compound. The surface layer can substantially or completely cover the carbon layer or partially cover the carbon layer.

[0059] As shown in FIG. 1, the carbon layer 2 exists on the surface of the silicon-containing composite particles 1, and the surface layer exists on the entire surface of the carbon layer 2. FIG. 1 shows the case where the surface layer is a thin film-like layer.

[0060] As shown in FIG. 2, the carbon layer 2 is present on the surface of the silicon-containing composite particles 1, and the surface layer is present on a part of the carbon layer 2. FIG. 2 shows the case where the surface layer is of the island type.

[0061] The surface layer may be provided on a region of the surface of the particles containing SiO x (0 < x < 2) and the Li compound where no carbon layer is provided. That is, the surface layer may be coated adjacent to the particles containing SiO x (0 < x < 2) and the Li compound, and may be provided in the form of particles - surface layer containing SiO x (0 < x < 2) and the Li compound.

[0062] As shown in FIG. 3, the carbon layer 2 and the surface layer 3 may be present in the overlapping and non - overlapping portions of the silicon-containing composite particles 1.

[0063] In one embodiment of the present invention, the negative electrode active material contains at least one Group 13 element and at least one Group 15 element. In one example, the Group 13 elements include B, Al, Ga, In, and Tl, and the Group 15 elements include N, P, As, Sb, and Bi.

[0064] In one embodiment of the present invention, the negative electrode active material contains Al and P.

[0065] In one embodiment of the present invention, the negative electrode active material contains B and P.

[0066] In one embodiment of the present invention, the negative electrode active material contains Li, at least one Group 13 element, and at least one Group 15 element.

[0067] In one embodiment of the present invention, the negative electrode active material contains Li, Al, and P.

[0068] In one embodiment of the present invention, the negative electrode active material contains Li, B, and P.

[0069] In one embodiment of the present invention, Li, a group 13 element, and a group 15 element may be detected during ICP analysis of the negative electrode active material. Specifically, the group 13 element may be Al or B, and the group 15 element may be P.

[0070] In one embodiment of the present invention, the surface layer may contain Al and P.

[0071] In one embodiment of the present invention, the surface layer may contain B and P.

[0072] In one embodiment of the present invention, the surface layer may contain Al, P and O elements.

[0073] In one embodiment of the present invention, the surface layer may contain B, P and O elements.

[0074] In one embodiment of the present invention, the surface layer may contain Li, Al, P and O elements.

[0075] In one embodiment of the present invention, the surface layer may contain Li, B, P and O elements.

[0076] In one embodiment of the present invention, the at least one Group 13 element may be contained in an amount of 0.05 to 0.3 parts by weight based on a total of 100 parts by weight of the negative electrode active material. Specifically, the at least one Group 13 element may be contained in an amount of 0.1 to 0.4 parts by weight, 0.12 to 0.35 parts by weight, or 0.15 to 0.3 parts by weight.

[0077] In one embodiment of the present invention, the at least one Group 15 element may be contained in an amount of 0.05 to 2 parts by weight based on a total of 100 parts by weight of the negative electrode active material. Specifically, the at least one Group 15 element may be contained in an amount of 0.1 to 1.5 parts by weight, or 0.15 to 1 part by weight.

[0078] The surface layer is Al z Pw O v may include a phase where (0 < z ≤ 10, 0 < w ≤ 10, 0 < v ≤ 10). The Al z P w O v phase may include aluminum oxide, phosphorus oxide, aluminum phosphate, etc., and z, w, and v represent the atomic number ratios. In one example, the Al z P w O v phase may include a mixture or compound formed from, for example, AlPO4 or Al(PO3)3, but is not limited thereto.

[0079] The surface layer may include a phase of Li y Al z P w O v (0 < y ≤ 10, 0 < z ≤ 10, 0 < w ≤ 10, 0 < v ≤ 10). The Li y Al z P w O v phase may include aluminum oxide, phosphorus oxide, lithium oxide, aluminum phosphate, lithium salt, lithium phosphate, lithium aluminate, etc., and y, z, w, and v represent the atomic number ratios. In one example, the Li y Al z P w O v phase may 、 include a mixture or compound formed from, for example, Li3PO4, AlPO4, Al(PO3)3, or LiAlO2, but is not limited thereto.

[0080] The surface layer may include a phase of B z1 P w1 O v1 (0 < z1 ≤ 10, 0 < w1 ≤ 10, 0 < v1 ≤ 10). The B z1 P w1 O v1 phase may include boron oxide, phosphorus oxide, boron phosphate, etc., and z1, w1, and v1 represent the atomic number ratios.

[0081] The surface layer contains Li y1 B z1 P w1 O v1 (0 < y1 ≤ 10, 0 < z1 ≤ 10, 0 < w1 ≤ 10, 0 < v1 ≤ 10) phase may be included. The Li y1 B z1 P w1 O v1 phase may include boron oxide, phosphorus oxide, lithium oxide, boron phosphate, lithium salt, lithium phosphate, lithium borate, etc. y1, z1, w1, and v1 represent the atomic number ratios.

[0082] When an inorganic surface layer containing such a phase is provided, the phenomenon that the Li compound contained in the silicon-containing composite particles reacts with the moisture in the slurry to lower the viscosity of the slurry can be prevented, and thus the stability of the electrode state and / or the charge-discharge capacity can be improved.

[0083] In one embodiment of the present invention, the surface layer may contain an amorphous phase.

[0084] In one embodiment of the present invention, the surface layer may be an amorphous phase.

[0085] The surface layer contains Al z P w O v (0 < z ≤ 10, 0 < w ≤ 10, 0 < v ≤ 10) phase may be included, and the Al z P w O v (0 < z ≤ 10, 0 < w ≤ 10, 0 < v ≤ 10) phase may be an amorphous phase.

[0086] The surface layer contains Li y Al z P w O v (0 < y ≤ 10, 0 < z ≤ 10, 0 < w ≤ 10, 0 < v ≤ 10) phase may be included, and the Li y Al z P w O v(0 < y ≤ 10, 0 < z ≤ 10, 0 < w ≤ 10, 0 < v ≤ 10) The phase may be an amorphous phase.

[0087] When the surface layer is composed of a crystalline material, there is a problem that it becomes difficult for Li ions to enter and exit, and the resistance and life characteristics deteriorate. Since the negative electrode active material of the present invention has a surface layer containing the amorphous phase as described above, the entry and exit of Li ions are easier than in the case of not containing the amorphous phase. Therefore, there is an effect of stably realizing the capacity and / or efficiency while effectively reducing side reactions on the slurry.

[0088] In one embodiment of the present invention, the surface layer may further contain at least one selected from the group consisting of Li2O, LiOH, and Li2CO3. Generally, in the process of doping silicon-containing particles with lithium, the remaining substances can be exposed to moisture and air to form lithium by-products such as Li2O, LiOH, and Li2CO3. Therefore, the surface layer may be in a form containing at least one selected from the group consisting of Li2O, LiOH, and Li2CO3.

[0089] In one embodiment of the present invention, the y may satisfy 0 < y ≤ 3.

[0090] In one embodiment of the present invention, the z may satisfy 0 < z ≤ 1.

[0091] In one embodiment of the present invention, the w may satisfy 0.5 ≤ w ≤ 3.

[0092] In one embodiment of the present invention, the v may satisfy 4 < v ≤ 12.

[0093] The surface layer can be formed by dry-mixing and heat-treating i) silicon-containing composite particles and aluminum phosphate, ii) silicon-containing composite particles, an aluminum precursor, and a phosphorus precursor, or iii) silicon-containing composite particles and a Li-Al-P-O-based precursor, or by mixing in a solvent and then reacting while vaporizing the solvent.

[0094] In one embodiment of the present invention, when performing X-ray diffraction analysis of the negative electrode active material, no crystalline peak derived from the surface layer appears. Specifically, Li y Al z P w O v (0 < y ≤ 10, 0 < z ≤ 10, 0 < w ≤ 10, 0 < v ≤ 10) crystalline peaks derived from the phase are not detected. When a crystalline peak derived from the surface layer appears, there is a problem that the surface layer contains an excessive amount of crystal, resulting in a decrease in capacity and / or efficiency. In one example, in the case of a crystalline peak derived from the surface layer, it can be recognized through the change before / after the surface layer coating. Specifically, in the case of XRD, when no difference in the XRD graph of the negative electrode active material before / after the surface layer coating is observed due to the detection of a crystalline peak, it means that no crystalline peak derived from the surface layer appears, and it can be confirmed that the surface layer is formed of an amorphous phase.

[0095] In one embodiment of the present invention, the amorphous phase contained in the surface layer may be contained in an amount exceeding 50 parts by weight based on 100 parts by weight in total of the surface layer. Specifically, the amorphous phase may be contained in an amount of 60 parts by weight or more, 70 parts by weight or more, 80 parts by weight or more, 90 parts by weight or more, 95 parts by weight or more, or 99 parts by weight or more based on 100 parts by weight in total of the surface layer, and may be contained in an amount of 100 parts by weight or less or less than 100 parts by weight. By satisfying the range exceeding 50 parts by weight as described above, side reactions on the slurry can be efficiently suppressed, and there is an effect that capacity and / or efficiency can be stably realized.

[0096] In one embodiment of the present invention, the surface layer may be included in an amount of 10 parts by weight or less based on a total of 100 parts by weight of the negative electrode active material. Specifically, the surface layer may be included in an amount of 8 parts by weight or less, 6 parts by weight or less, or 5 parts by weight or less, or 0.1 parts by weight or more, or 0.5 parts by weight or more. More specifically, the surface layer may be included in an amount of 1 part by weight or more and 5 parts by weight or less, or 1.5 parts by weight or more and 3 parts by weight or less. If the surface layer content is less than the above range (e.g., less than 0.1 parts by weight), it is difficult to prevent gas generation on the slurry, and if the surface layer content is more than the above range (e.g., more than 10 parts by weight), it is difficult to realize the capacity and efficiency.

[0097] In one embodiment of the present invention, the weight ratio of the surface layer to the carbon layer may be 1:0.1 to 1:30. Specifically, it may be 1:0.5 to 1:5, 1:1 to 1:4, or 1:1 to 1:3. By satisfying the above range, the carbon layer and the surface layer effectively cover the silicon-containing composite particles, and side reactions on the slurry can be efficiently suppressed, so that capacity and / or efficiency can be stably realized. On the other hand, if the content of the surface layer is too high compared to the carbon layer, it is difficult to realize the capacity or efficiency, and if the content of the carbon layer is too high compared to the surface layer, it is difficult to prevent gas generation on the slurry.

[0098] In one embodiment of the present invention, the surface layer may be included in an amount of 90 parts by weight or less based on 100 parts by weight of the carbon layer. Specifically, the surface layer may be included in an amount of 80 parts by weight or less, 70 parts by weight or less, 60 parts by weight or less, or 50 parts by weight or less based on 100 parts by weight of the carbon layer. In addition, the surface layer may be included in an amount of 0.1 parts by weight or more, 1 part by weight or more, 5 parts by weight or more, or 10 parts by weight or more based on 100 parts by weight of the carbon layer. By satisfying the above range, the carbon layer and the surface layer can effectively cover the silicon-containing composite particles, thereby efficiently suppressing side reactions in the slurry, and stably realizing the capacity and / or efficiency.

[0099] The average particle size (D 50) may be 0.1 μm to 30 μm, specifically 1 μm to 20 μm, and more specifically 1 μm to 10 μm. When the range of 0.1 μm to 30 μm is satisfied, the structure of the active material during charging and discharging can be stabilized, the problem of the volume expansion / contraction level increasing as the average particle size becomes excessively large can be prevented, and the problem of the initial efficiency decreasing as the average particle size becomes excessively small can be prevented.

[0100] <Method of manufacturing negative electrode active material> In one embodiment of the present invention, the method for producing the negative electrode active material includes the steps of producing silicon-containing composite particles; and providing a surface layer on at least a portion of the silicon-containing composite particles.

[0101] The silicon-containing composite particles may be formed through the steps of: vaporizing Si powder and SiO powder by heating in a vacuum, and then depositing the vaporized mixed gas to form preliminary particles; forming a carbon layer on the preliminary particles; and mixing the preliminary particles on which the carbon layer is formed with Li powder and then heat treating the mixture.

[0102] Alternatively, the silicon-containing composite particles may be formed by the steps of: heating and vaporizing Si powder and SiO2 powder in a vacuum, and then depositing the vaporized mixed gas to form preliminary particles; and mixing the preliminary particles with Li powder, followed by heat treatment.

[0103] Specifically, the mixed powder of the Si powder and the SiO2 powder can be heat treated at 1400°C to 1800°C or 1400°C to 1600°C under vacuum.

[0104] The preliminary particles formed are SiO x It can exist in the form (x=1).

[0105] The silicon-containing composite particles may contain the above-mentioned Li silicate, Li silicide, Li oxide, and the like.

[0106] The particle size of the silicon-containing composite particles can be adjusted by a method such as, but not limited to, a ball mill, a jet mill, or air flow classification.

[0107] In the step of forming the carbon layer, a chemical vapor deposition (CVD) method using a hydrocarbon gas may be used, or a carbon source material may be carbonized to form the carbon layer.

[0108] Specifically, the preliminary particles are fed into a reactor, and then a hydrocarbon gas is subjected to chemical vapor deposition (CVD) at 600° C. to 1200° C. The hydrocarbon gas is at least one type of hydrocarbon gas selected from the group including methane, ethane, propane, and acetylene, and can be heat-treated at 900° C. to 1000° C.

[0109] In one embodiment of the present specification, the step of providing a surface layer on at least a portion of the silicon-containing composite particle may include a step of mixing and reacting the silicon-containing composite particle with a precursor containing a Group 13 element and a Group 15 element.

[0110] The group 13 element may be Al or B.

[0111] The group 15 element may be P.

[0112] The precursor containing a Group 13 element and a Group 15 element may be an aluminum phosphate or a boron phosphate.

[0113] The step of providing a surface layer on at least a part of the silicon-containing composite particles may include a step of dry mixing and heat-treating the silicon-containing composite particles and the aluminum phosphate, or a step of mixing the silicon-containing composite particles and the aluminum phosphate in a solvent and then reacting the silicon-containing composite particles and the aluminum phosphate while heat-treating to vaporize the solvent. When forming the surface layer by the method, the Li by-product formed in the manufacturing process of the silicon-containing composite particles can be reacted with the aluminum phosphate to easily form the surface layer.

[0114] The aluminum phosphate is Al b P c O d It may be in the form of (0 < b ≤ 10, 0 < c ≤ 10, 0 < d ≤ 10). Specifically, it may be Al(PO3)3 or AlPO4, but is not limited thereto, and salts used in the art for forming the surface layer may be appropriately employed.

[0115] The boron phosphate is B b1 P c1 O d1 It may be in the form of (0 < b1 ≤ 10, 0 < c1 ≤ 10, 0 < d1 ≤ 10).

[0116] In another embodiment, the step of providing a surface layer on at least a part of the silicon-containing composite particles may include a step of mixing and reacting the silicon-containing composite particles, a precursor containing a Group 13 element, and a precursor containing a Group 15 element.

[0117] The precursor containing the Group 15 element may be a phosphorus precursor.

[0118] Specifically, the step of providing a surface layer on at least a part of the silicon-containing composite particles may include dry-mixing and heat-treating the silicon-containing composite particles, a precursor containing a Group 13 element, and a phosphorus precursor, or mixing the silicon-containing composite particles, a precursor containing a Group 13 element, and a phosphorus precursor in a solvent and then reacting the silicon-containing composite particles, the precursor containing a Group 13 element, and the phosphorus precursor while heat-treating to vaporize the solvent. When forming the surface layer by the method, it is possible to easily form the surface layer by reacting Li by-products, a precursor containing a Group 13 element, and a phosphorus precursor formed during the production process of the silicon-containing composite particles.

[0119] The precursor containing a Group 13 element may be an aluminum precursor or a boron precursor.

[0120] The aluminum precursor is Al a O b aluminum oxide in the form of (0 < a ≤ 10, 0 < b ≤ 10), and specifically may be Al2O3.

[0121] Or 、 The aluminum precursor may be aluminum hydroxide, aluminum nitrate, aluminum sulfate, etc., and specifically may be Al(OH)3, Al(NO3)3·9H2O, or Al2(SO4)3, and is not limited thereto. Aluminum precursors used in the industry for forming the surface layer can be appropriately adopted.

[0122] The boron precursor may be B(OH)3, (BOH)3O3, H2B4O7, etc., and is not limited thereto. Boron precursors used in the industry for forming the surface layer can be appropriately adopted.

[0123] The phosphorus precursor is P c O d phosphorus oxide in the form of (0 < c ≤ 10, 0 < d ≤ 10).

[0124] Alternatively, the phosphorus precursor is ammonium phosphate, diammonium phosphate, phosphoric acid, etc. Specifically, it may be (NH4)3PO4, (NH4)2HPO 4、 H3PO4, or NH4H2PO4, and is not limited thereto. A phosphorus precursor used in the art for forming the surface layer can be appropriately employed.

[0125] Alternatively, the step of providing a surface layer on at least a part of the silicon-containing composite particles may include a step of dry-mixing and heat-treating the silicon-containing composite particles and the Li-Al-P-O-based precursor, or a step of mixing the silicon-containing composite particles and the Li-Al-P-O-based precursor in a solvent and then heat-treating to react the silicon-containing composite particles and the Li-Al-P-O-based precursor while vaporizing the solvent. When forming the surface layer by the above method, the Li-Al-P-O series precursor can be directly introduced to form the surface layer.

[0126] The Li-Al-P-O-based precursor is Li y Al z P w O v (0 < y ≤ 10, 0 < z ≤ 10, 0 < w ≤ 10, 0 < v ≤ 10). Specifically, it may be a mixture or compound formed complexly from Li3PO4, AlPO4, Al(PO3)3, LiAlO2, etc., and is not limited thereto. A configuration used in the art for forming the surface layer can be appropriately employed.

[0127] In the step of providing a surface layer on at least a part of the silicon-containing composite particles, the heat treatment may be performed at 500°C to 700°C, specifically, it can be performed at 550°C to 650°C. However, it is not limited thereto and may vary depending on the salt or precursor used. When the heat treatment temperature is higher than the range of 500°C to 700°C, the surface layer is formed in a crystalline state, making it difficult for Li ions to enter and exit through the surface layer. As a result, there are problems such as a decrease in resistance and life characteristics, and a decrease in capacity and / or efficiency. When the heat treatment temperature satisfies the range of 500°C to 700°C, the reaction between the salt or precursor and the Li by-product occurs well, and the surface layer contains Li. Therefore, the durability of the formed negative electrode active material against moisture is increased, the lithium diffusion resistance on the surface of the negative electrode active material is decreased, and there is an effect of excellent rate capability.

[0128] The solvent may be water or ethanol, and is not limited thereto. Solvents used in the industry can be appropriately adopted.

[0129] The surface layer formed on the silicon-containing composite particles preferably contains Li y Al z P w O v (0 < y ≤ 10, 0 < z ≤ 10, 0 < w ≤ 10, 0 < v ≤ 10) phase, and the Li y Al z P w O v phase may be an amorphous phase.

[0130] The content regarding the surface layer is as described above.

[0131] <Negative electrode> The negative electrode according to an embodiment of the present invention may include the above-described negative electrode active material.

[0132] Specifically, the negative electrode may include a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector. The negative electrode active material layer may include the negative electrode active material. Furthermore, the negative electrode active material layer may further include a binder and / or a conductive material.

[0133] The negative electrode active material layer may be formed by applying a negative electrode slurry containing a negative electrode active material, a binder and / or a conductive material to at least one surface of a negative electrode current collector, followed by drying and rolling.

[0134] The negative electrode slurry contains the negative electrode active material, a binder and / or a conductive material.

[0135] The negative electrode slurry may further include an additional negative electrode active material.

[0136] The additional negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the additional negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon; metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys; SiO β(0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, lithium titanium oxide, and lithium vanadium oxide; or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites or Sn-C composites, and any one or a mixture of two or more of these may be used. In addition, a metallic lithium thin film may be used as the negative electrode active material. In addition, both low-crystalline carbon and high-crystalline carbon may be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, while representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural or artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0137] The additional anode active material may be a carbon-containing anode active material.

[0138] In one embodiment of the present invention, the weight ratio of the negative electrode active material and the additional negative electrode active material contained in the negative electrode slurry may be 10:90 to 90:10, specifically, 10:90 to 50:50.

[0139] The negative electrode current collector is not particularly limited as long as it is conductive and does not induce chemical changes in the battery. For example, the current collector may be made of copper, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, or the like. Specifically, transition metals that easily adsorb carbon, such as copper and nickel, can be used as the current collector. The thickness of the current collector may be 6 μm to 20 μm, but is not limited thereto.

[0140] The binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.

[0141] The conductive material is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and examples of the conductive material that may be used include graphite such as natural graphite and artificial graphite; carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black; conductive fibers such as carbon fibers and metal fibers; conductive tubes such as carbon nanotubes; fluorocarbons; metal powders such as aluminum and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; and conductive materials such as polyphenylene derivatives.

[0142] The negative electrode slurry according to an embodiment of the present invention may further include a solvent for forming a negative electrode slurry. Specifically, the solvent for forming a negative electrode slurry may include at least one selected from the group consisting of distilled water, ethanol, methanol, and isopropyl alcohol, specifically, distilled water, in order to facilitate dispersion of the components.

[0143] In one embodiment of the present invention, the solid content weight of the negative electrode slurry may be 20 parts by weight to 75 parts by weight, specifically 30 parts by weight to 70 parts by weight, based on a total of 100 parts by weight of the negative electrode slurry.

[0144] <Secondary battery> A secondary battery according to an embodiment of the present invention may include the anode according to the embodiment described above. Specifically, the secondary battery may include an anode, a cathode, a separator and an electrolyte interposed between the cathode and the anode, and the anode is the same as the anode described above. The anode has been described above, so a detailed description thereof will be omitted.

[0145] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on at least one surface of the positive electrode current collector and including the positive electrode active material.

[0146] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. may be used. In addition, the positive electrode current collector may usually have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the collector surface to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0147] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≦c2≦0.3); 2-c3 M c3 Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be Li metal.

[0148] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.

[0149] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular restrictions as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber, and other carbon-containing substances; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.

[0150] The positive electrode binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer rubber (EPDM), sulfonated-EPDM, styrene butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.

[0151] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in secondary batteries can be used without any particular restrictions. In particular, a separator that has low resistance to ion movement of the electrolyte and excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc., may be used. In addition, a coated separator containing a ceramic component or a polymeric substance may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.

[0152] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.

[0153] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.

[0154] Examples of the non-aqueous organic solvent include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.

[0155] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, are preferably used since they are high-viscosity organic solvents with high dielectric constants and dissociate lithium salts well. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore these cyclic carbonates are more preferably used.

[0156] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3- , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of:

[0157] In addition to the constituent components of the electrolyte, the electrolyte may further contain one or more additives such as a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ether, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.

[0158] According to another embodiment of the present invention, there is provided a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate-limiting characteristics and high cycle characteristics, and therefore can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems.

[0159] [Example] In the following, preferred embodiments are presented to aid in understanding the present invention, but the above embodiments are merely illustrative of the present invention, and it is obvious to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the present invention. It is natural that such changes and modifications fall within the scope of the accompanying claims.

[0160] (Example 1-1) 100 g of a powder of Si and SiO2 mixed in a 1:1 molar ratio was vacuum heated in a reactor at a sublimation temperature of 1,400°C. The vaporized Si and SiO2 mixed gas was then reacted in a vacuum cooling zone with a cooling temperature of 800°C to solidify. Then, a heat treatment was carried out in an inert atmosphere at a temperature of 800°C to produce preliminary silicon-containing particles. The preliminary silicon-containing particles were then milled for 3 hours into a powder of 6 μm (D 50 The silicon-containing particles were then placed in the hot zone of a CVD apparatus while maintaining an inert atmosphere by flowing Ar gas, and the methane was blown into the hot zone at 900° C. using Ar as a carrier gas, and the methane was heated for 20 minutes at 100° C. -1 The reaction was carried out at torr to form a carbon layer on the surface of the silicon-containing particles.

[0161] 10 g of Li metal powder was added to 90 g of the silicon-containing particles, and heat treatment was carried out at a temperature of 800° C. in an inert atmosphere to prepare Li-doped silicon-containing composite particles.

[0162] 98.5 g of the silicon-containing composite particles were mixed with 1.5 g of Al(PO3)3, and then heat-treated at 600° C. to prepare a negative active material having a surface layer containing Li, Al, P, and O formed on the surface of the silicon-containing composite particles. 50 The BET specific surface area is 2.5m 2 / g.

[0163] When the negative active material was subjected to ICP analysis, the contents of Li, Al, and P were 9.5 wt%, 0.15 wt%, and 0.5 wt%, respectively, based on a total of 100 wt% of the negative active material.

[0164] (Example 1-2) The negative active material was prepared in the same manner as in Example 1-1, except that AlPO4 was used instead of Al(PO3)3. 50 The BET specific surface area is 2.5m 2 / g.

[0165] When the negative active material was subjected to ICP analysis, the contents of Li, Al, and P were 9.5 wt%, 0.15 wt%, and 0.17 wt%, respectively, based on a total of 100 wt% of the negative active material.

[0166] (Examples 1-3) The negative active material was prepared in the same manner as in Example 1-1, except that 97 g of the silicon-containing composite particles and 33 g of Al(PO3)3 were used. 50 The BET specific surface area is 2.5m 2 / g.

[0167] When the negative active material was subjected to ICP analysis, the contents of Li, Al, and P were 9.4 wt%, 0.3 wt%, and 0.9 wt%, respectively, based on a total of 100 wt% of the negative active material.

[0168] (Comparative Example 1-1) The negative electrode active material was prepared in the same manner as in Example 1-1, except that the heat treatment temperature during the formation of the surface layer was 800° C. 50 The BET specific surface area is 2.5m 2 / g.

[0169] (Comparative Example 1-2) The negative active material was prepared in the same manner as in Example 1-1, except that Al(PO3)3 was not mixed into the silicon-containing composite particles. 50The BET specific surface area is 2.5m 2 / g.

[0170] The negative electrode active materials prepared in the above examples and comparative examples are as shown in Table 1 below.

[0171] [Table 1]

[0172] The Li, Al, and P atom contents were confirmed by ICP analysis using an inductively coupled plasma optical emission spectrometer (Perkin-Elmer 7300 ICP-OES, AVIO 500).

[0173] The phase of the surface layer was confirmed by the change in the XRD graph before and after the surface layer coating. When the surface layer was amorphous, there was no difference in the XRD pattern before and after the coating.

[0174] The content of the carbon layer was confirmed under oxygen conditions through elemental analysis by combustion (Bruker's G4 ICARUS).

[0175] D of the negative electrode active material 50 was analyzed by PSD measurement method using a microtac device.

[0176] The specific surface area was measured by degassing at 200° C. for 8 hours and performing N 2 adsorption / desorption at 77K using a BET measuring device (BEL-SORP-MAX, Nippon Bell).

[0177] <Experimental Example 1: Evaluation of discharge capacity, initial efficiency and capacity retention rate> Negative electrodes and batteries were fabricated using the negative electrode active materials of the examples and comparative examples, respectively.

[0178] The negative electrode active material, carbon black as a conductive material, and PAA (poly acrylic acid) as a binder were mixed in a weight ratio of 80:10:10 to prepare a mixture. Then, 7.8g of distilled water was added to 5g of the mixture and stirred to prepare a negative electrode slurry. The negative electrode slurry was applied to one side of a copper (Cu) metal thin film as a negative electrode current collector having a thickness of 20μm, and dried. The temperature of the circulating air was 60°C. Then, the mixture was rolled and dried in a vacuum oven at 130°C for 12 hours to prepare a negative electrode.

[0179] 1 .7671cm 2 The lithium (Li) metal thin film cut into a circular shape was used as the positive electrode. A porous polyethylene separator was placed between the positive electrode and the negative electrode, and an electrolyte solution in which 0.5 parts by weight of vinylene carbonate was dissolved in a mixed solution of methyl ethyl carbonate (EMC) and ethylene carbonate (EC) with a volume ratio of 7:3, and LiPF6 was dissolved at a concentration of 1M was injected to manufacture a lithium coin half-cell.

[0180] The produced batteries were charged and discharged, and the discharge capacity, initial efficiency, and capacity retention rate were evaluated. The results are shown in Table 2 below.

[0181] The first and second cycles were charged and discharged at 0.1 C, and the third to 49th cycles were charged and discharged at 0.5 C. The 50th cycle was completed in a charged state (with lithium contained in the negative electrode).

[0182] Charging conditions: CC (constant current) / CV (constant voltage) (5mV / 0.005C current cut-off) Discharge condition: CC (constant current) condition 1.5V

[0183] The discharge capacity (mAh / g) and initial efficiency (%) were derived from the results of one charge / discharge. Specifically, the initial efficiency (%) was calculated as follows: Initial efficiency (%) = (discharge capacity after one discharge / one charge capacity) × 100

[0184] The capacity retention rates were calculated as follows. Capacity retention rate (%) = (50 discharge capacity / 1 discharge capacity) × 100

[0185] [Table 2]

[0186] In Table 2, in Examples 1-1 to 1-3, it can be seen that the surface layer formed as an amorphous phase on the silicon-containing composite particles effectively removes lithium by-products contained in the silicon-containing composite particles, and the surface layer effectively covers the silicon-containing composite particles to prevent the lithium by-products and the lithium compounds of the silicon-containing composite particles from reacting with the moisture in the slurry to degrade the physical properties of the slurry, resulting in excellent discharge capacity, initial efficiency, and capacity retention.

[0187] On the other hand, in Comparative Example 1-1, the heat treatment temperature was high and the surface layer was formed of a crystalline material, which made it difficult for Li ions to enter and exit, and it was confirmed that the discharge capacity, initial efficiency, and life characteristics were reduced.

[0188] Comparative Example 1-2 did not include a surface layer, and it was confirmed that the Li compound contained in the silicon-containing composite particles easily reacted with the moisture in the slurry to change the viscosity of the slurry and cause side reactions in the slurry, resulting in a decrease in initial efficiency and life characteristics.

[0189] (Example 2-1) A negative active material having a surface layer containing Al, P, and O was prepared in the same manner as in Example 1-1, except that the silicon-containing composite particles and Al(PO3)3 were dispersed in ethanol and then heated to 90°C to evaporate the ethanol.

[0190] The surface layer of the negative electrode active material formed was amorphous, and the content of the surface layer was 1.5 parts by weight, the carbon layer was 4.5 parts by weight, and Li was 9.5 parts by weight, based on a total of 100 parts by weight of the negative electrode active material. 50 is 6μm, and the specific surface area is 2.5m 2 / g.

[0191] <Experimental example 2: Speed ​​characteristic evaluation> A negative electrode and a battery were fabricated in the same manner as in Experimental Example 1 using the negative electrode active materials of Example 1-1 and Example 2-1.

[0192] The charge / discharge of the batteries prepared in Example 1-1 and Example 2-1 was evaluated. The charge rate was fixed at 0.2C, and the discharge rate was changed to 0.2C, 1.0C, 3.0C, and 5.0C. In order to confirm how much the discharge capacity decreased, the rate capability was measured and the results are shown in Table 3 below. Meanwhile, the discharge capacity at the time of discharging at 0.2C was set to 100%.

[0193] [Table 3]

[0194] In the above-mentioned Examples 1-1 and 2-1, the surface layer is formed of an amorphous phase on the surface of the silicon-containing composite particle, and thus the surface layer effectively covers the silicon-containing composite particle and prevents the lithium by-products and the lithium compound of the silicon-containing composite particle from reacting with the moisture in the slurry to deteriorate the physical properties of the slurry.

[0195] Among them, Example 2-1 does not contain Li in the surface layer, whereas Example 1-1 contains Li in the surface layer, and therefore the lithium diffusion resistance on the surface of the negative electrode active material is low and the discharge rate capability is excellent. Therefore, it was confirmed that Example 1-1 has a better discharge capacity according to the discharge rate than Example 2-1.

Claims

1. SiO x (0<x<2) and a silicon-containing composite particle comprising a Li compound; a carbon layer on at least a portion of a surface of the silicon-containing composite particle; a surface layer comprising an amorphous phase on at least a portion of the silicon-containing composite particle; and at least one Group 13 element and at least one Group 15 element; a negative electrode active material, wherein the surface layer contains an AlzPwOv (0<z≦10, 0<w≦10, 0<v≦10) phase or a LiyAlzPwOv (0<y≦10, 0<z≦10, 0<w≦10, 0<v≦10) phase, and the AlzPwOv phase or the LiyAlzPwOv phase is an amorphous phase.

2. The negative electrode active material according to claim 1 , wherein the surface layer contains Al, P and O elements.

3. The negative electrode active material according to claim 1 , wherein the surface layer contains Li, Al, P and O elements.

4. The surface layer is Li y A z P w O v (0<y≦10, 0<z≦10, 0<w≦10, 0<v≦10) phase, The Li y A z P w O v 2. The negative electrode active material of claim 1, wherein the phase is an amorphous phase.

5. The negative electrode active material according to claim 1 , wherein no crystalline peak derived from a surface layer appears in an X-ray diffraction analysis of the negative electrode active material.

6. During X-ray diffraction analysis of the negative electrode active material, a peak due to Si appears, and a peak due to Li 2 SiO 3 and Li 2 S 2 O 5 The negative electrode active material according to claim 1 , wherein a peak due to at least one of the following appears.

7. The negative electrode active material according to claim 1 , wherein the amorphous phase contained in the surface layer is contained in an amount of more than 50 parts by weight based on a total of 100 parts by weight of the surface layer.

8. 2. The negative electrode active material according to claim 1, wherein a weight ratio of the surface layer to the carbon layer is 1:0.1 to 1:

30.

9. The negative electrode active material of claim 1 , wherein the surface layer is present in an amount of 90 parts by weight or less based on 100 parts by weight of the carbon layer.

10. The surface layer is Li 2 O, LiOH and Li 2 CO 3 The negative electrode active material according to claim 1 , further comprising at least one selected from the group consisting of:

11. The negative electrode active material according to claim 1, wherein Li is contained in an amount of 0.1 to 25 parts by weight based on a total of 100 parts by weight of the negative electrode active material.

12. The negative electrode active material according to claim 1 , wherein the carbon layer includes an amorphous phase.

13. The negative electrode active material of claim 1 , wherein the carbon layer is included in an amount of 0.1 to 50 parts by weight based on a total of 100 parts by weight of the negative electrode active material.

14. 2. The negative electrode active material of claim 1, wherein the surface layer is present on an outer surface of at least a portion of the carbon layer.

15. The negative electrode active material according to claim 1 , wherein the surface layer is present on an area of ​​the particle surface where the carbon layer is not provided.

16. A negative electrode comprising the negative electrode active material of claim 1.

17. A secondary battery comprising the negative electrode according to claim 16.

Citation Information

Patent Citations

  • Negative electrode active material for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery, and method for manufacturing negative electrode material for nonaqueous electrolyte secondary battery

    JP2017010645A

  • Negative electrode active material for nonaqueous electrolyte secondary battery, nonaqueous electrolyte secondary battery, and method for manufacturing negative electrode material for nonaqueous electrolyte secondary battery

    JP2017152358A

  • Negative electrode active material, mixing negative electrode active material, and method of manufacturing negative electrode active material

    JP2018060771A

  • Negative electrode active material for lithium ion secondary battery, negative electrode, and lithium ion secondary battery

    JP2018170250A

  • Negative electrode active material, mixture negative electrode active material, water type negative electrode slurry composition, and manufacturing method of the negative electrode active material

    JP2020077510A